Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Test - Page 561: 11



Work Step by Step

$\frac{y^{2}-5y+6}{2y+4}\times\frac{y+2}{2y-6}$ =$\frac{y^{2}-2y-3y+6}{2(y+2)}\times\frac{y+2}{2(y-3)}$ =$\frac{y(y-2)-3(y-2)}{2(1)}\times\frac{1}{2(y-3)}$ =$\frac{(y-2)(y-3)}{2(1)}\times\frac{1}{2(y-3)}$ =$\frac{(y-2)}{2(1)}\times\frac{1}{2}$ =$\frac{(y-2)}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.